NIC 2 análisis de costos de transformación y medición de su rentabilidad en cantera ubicada en Las Lojas - Tamayo Torres, Roosevelt Javier (2023)
This project focuses on the analysis and evaluation of a quarry that provides materials for construction located in the Lojas sector, this market is very exploited, due to the importance that these materials generate for the construction of new buildings for the city or private homes; it was observed that in the quarry located in Las Lojas, they do not have a cost and inventory control, which allows to better help the profitability in that business. For this reason it was decided to make the proposal for the application of a cost and inventory center within the quarry, this will allow to increase or increase the profitability of the company, through the implementation of these elements it will be possible to obtain a more precise cost generated by the processing of each of the materials they sell and in turn it will be possible to better control and measure the waste thrown by Of each process, in order to reduce the margin of waste that can be obtained in that quarry, being indifferent to the material that is being made. It is expected to obtain a 20% increase in profit margin by applying this inventory control and in turn cost control.